Preparing for end of service life of wind turbines (2013)
The wind power industry is growing rapidly. Wind turbines (WTs) are perceived as a low environmental impact energy generation technology. While the service life of a WT is relatively long (20-40 years), at some point a significant number of WTs will reach the end of their service lives. To recover maximum value from these WTs, planning for the end-of-service life of wind turbines (EOSLWTs) is paramount. Historically, environmental life cycle assessments of WTs have often only considered the materials extraction and processing, manufacturing, and use phases, leaving the management of EOSLWTs outside the scope of their attention. Four key EOSLWTs issues that are essential for the continuing development of wind energy technologies are presented: i) The challenges of managing of EOSLWTs given the fast growth rate of the industry and the large number of existing installed WTs; ii) The EOSLWT alternatives such as remanufacturing and recycling to recover functional and material value respectively; iii) The critical activities in the WT reverse supply chain such as recovery methods, logistics of transportation, quality of returns, and quality of reprocessed WTs; and iv) The economic and business issues associated with EOSLWTs. It is expected that the discussion provided will stimulate a dialog among decision makers and raise awareness of economic opportunities and unanticipated challenges in the wind power industry. © 2012 Elsevier Ltd. All rights reserved.